Peran Suami dan Istri dalam Rumah Tangga Islam - Fahmi, Zulkifli (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2023)
The role of husband and wife in a household is urgent in Islam, but in reality, the division of roles between husband and wife remains a problem in Muslim communities. Yet Islam has provided guidance and instructions about this matter from its original sources, the Quran and Hadith, as well as through the explanations of scholars. One of the notable scholars from Indonesia, is Sheikh Nawawi. He wrote a special book that discusses the relationship between husband and wife in the household, called Uqudullujjain. In this study, a qualitative-descriptive method was used with a literature review approach. The researcher used a descriptive method to unravel, interpret, and analyze data. From this research, it was found that in Sheikh Nawawi's view, the rights and obligations of husband and wife are very important to be understood in order to build a happy family. In this division of roles, the husband plays the role of the leader of the family, breadwinner, educator and teacher for his wife. Meanwhile, the role of the wife is as a companion to her husband who must be obedient except in sin, house manager, and partner to her husband in achieving life goals.